Comparison and predicted equation of energy expenditure during walking or running among Caucasians, African Americans and Asians - Xi Jin; Teresa Carithers; Mark Loftin (Sports Medicine and Health Science, 2021)
Knowledge of measured energy expenditure (EE) during walking and running is important for exercise prescription. Further, research on the EE comparison and EE predicted equation during walking or running among different ethnicities is limited. The purpose of the current study was to compare EE to walk or run 1 mile in Caucasian, African American and Asian adults and to develop a regression equation to predict EE to walk or run 1 mile. Two hundred and twenty-four participants were included (71 Caucasians, 68 African Americans and 85 Asians) with 3 groups (normal weight walking, overweight walking and running). EE was measured via indirect calorimetry. Analysis of variance was used to compare EE across groups. Multiple regression analysis was employed for EE prediction, and the prediction equation was cross-validated. A significant EE difference was found between walking and running among three ethnicities. The prediction equation was: EE ​= ​0.978 Body Weight – 4.571 Gender (male=1; female=2) ​+ ​3.524 Ethnicities (Caucasians=1, African Americans=2, Asians=3) ​+ ​32.447 (standard error of estimate=12.5 ​kcal·mile−1). The equation was valid through cross-validation, so it is recommended to apply for calculating EE during walking or running 1 mile among Caucasians, African Americans and Asians.